Entrepreneurship in small agricultural quick-impact enterprises in Iran: Development of an index, effective factors and obstacles - Kurosh Rezaei-Moghaddam; Hoda Izadi (Journal of Global Entrepreneurship Research, 2019)
Small enterprises are one of the most effective factors in the development of each country's economic and social systems, having the ability to compete with large industries, so these enterprises are mainly focused by authorities. This study aimed to develop indicators of entrepreneurship in rural small enterprises as well as identifying the effective factors and obstacles to provide strategies of entrepreneurship development. The population of study included small business owners in Fars Province, Iran that initiated business in rural areas through quick-impact enterprises project. Developing entrepreneurship index was conducted using the Delphi method and was tested using survey method. Data were gathered through interviews and questionnaires. According to the results of study, entrepreneurship development index in quick-impact enterprises includes 11 components affected by individuals, organizations and environment. Based on the results, management skills, knowledge management, business environment, self-managed training, and government policies are predictors of changes of entrepreneurship development in quick-impact enterprises. Additionally, factor analysis indicated five obstacles in development of entrepreneurship in quick-impact enterprises, including financial problems, market orientation, weakness of information, poor and inappropriate business environment and weakness in supportive government policies. Finally, some applicable recommendations were presented based on the study results.
Keywords: 650; Entrepreneurship development; Index; Quick-impact enterprises; Agriculture; Iran